Insights into Global Health Practice from the Agile Software Development Movement - David Flood; Anita Chary; Kirsten Austad; Anne Kraemer Diaz; Pablo García; Boris Martinez; Waleska López Canú; Peter Rohloff (Taylor & Francis Group, 2016)
Global health practitioners may feel frustration that current models of global health research, delivery, and implementation are overly focused on specific interventions, slow to provide health services in the field, and relatively ill-equipped to adapt to local contexts. Adapting design principles from the agile software development movement, we propose an analogous approach to designing global health programs that emphasizes tight integration between research and implementation, early involvement of ground-level health workers and program beneficiaries, and rapid cycles of iterative program improvement. Using examples from our own fieldwork, we illustrate the potential of 'agile global health' and reflect on the limitations, trade-offs, and implications of this approach.